Contemporary bayesian and frequentist statistical research methods for natural resource scientists - Stauffer, Howard B. (John Wiley & Sons, 2008)
The book provides case studies illustrating common problems that exist in the natural resource sciences and presents the statistical knowledge and tools needed for a modern treatment of these issues